In The Poetry Kingdom, Is Rhyme Always Queen? Translation Of Educational Proverb In A Poem: A Pace Towards Intercultural Communication - chemini, rokia (El Omda in Linguistics and Discourse Analysis, 2024)
Proverbs are known for their effective impact in the educational field .This study deals with the translation of proverbs included in a poem. On what basis should the translator make his decision while translating? Can he (she) translate any proverb literally? Or has he to provide an equivalent making sure it does exist before starting the translation? If it is the case, are the dictionaries available about that very period of time? Moreover, what would the reader of the poetic translation lose or gain when knowing or ignoring that what he is reading in a musical and coherent rhymed poem is not an equivalent of the proverb about which he does not know, or even ignores its language? For this aim, we have chosen as samples some French Proverbs in Les Fables de Jean La Fontaine with their Arabic & English translations , all three aiming at communicating advice and experiences. Which decision was made by each translator? And which characteristics were, first, taken into consideration: Poetry or proverb characteristics?